A new record of the damselfish chromis ovatiformis (fowler) (perciformes pomacentridae), from the Philippines - Hilomen, Vincent V. (1990)
The damselfish chromis ovatiformis is recorded for the first time in Puerto Galera, Oriental MIndoro, Philippines from three specimens. The new record brings the total number of the local species of chromis to 12 and extends the range of the species further south to the Philippines (13degrees N).